Pelatihan Penyusunan Modul Ajar Berbasis Literasi dan Numerasi Guru Sekolah Dasar Menggunakan Kecerdasan Buatan di Kecamatan Banyakan - Kurnia, Ita; Hunaifi, Abdul Aziz; Basori, Muhamad; Aulia, Astin Hadiahti; Istiqomah, Rohma Darul; Asfia, Vifi (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2025)
Literacy and numeracy are fundamental skills that are crucial for the development of elementary school-aged children. However, there are many challenges faced in improving the quality of learning in Banyakan District. This is reflected in the results of the Minimum Competency Assessment (AKM), which show that many literacy and numeracy outcomes are still low. To address this issue, the Elementary School Teacher Education Program (PGSD) at Universitas Nusantara PGRI Kediri collaborates with the Teacher Activity Group (KKG) to conduct training on developing literacy and numeracy-based teaching modules using artificial intelligence (AI). This training aims to enhance teachers' competencies in creating interactive and adaptive teaching modules and applying technology in the learning process. The results of this activity indicate that teacher participation in the training reached 97.68%, and it is expected to have a significant impact on student learning outcomes. This program is anticipated to provide a transformation in teaching literacy and numeracy and serve as a model for other districts to integrate technology into education. The sustainability of the program is planned through replication in other areas and collaboration with external parties to support the development of quality education